Metabolic syndrome is associated with increased cardiovascular risk and disease damage in patients with Takayasu arteritis - DİRESKENELİ, RAFİ HANER; ALİBAZ ÖNER, FATMA (My University, 2022)
Objective: Metabolic syndrome (MetS) is one of the preventable risk factors for cardiovascular disease (CVD). The aim of this study was to investigate the effect of MetS on CVD and cumulative organ damage in a multi-center, large cohort of patients with Takayasu arteritis (TAK). Methods: This is a cross-sectional study involving 192 consecutive TAK patients from seven tertiary rheumatology centers in Turkey. Clinical data of TAK patients fulfilling the 1990 American College of Rheumatology classification criteria were collected from medical records. They were evaluated for risk factors of CVD, disease activity, damage, and MetS at their last visits. Results: A total of 192 consecutive TAK patients were included in this study. One hundred and fifty-eight (82%) were female, the mean age was 43.3 ± 13 years, and mean disease duration was 13.5 ± 9.3 years. MetS was detected in 50 (26%) of the patients and CVD was detected in 28 (14.6%). The presence of MetS was detected as an independent risk factor for CVD (P < 0.001). In addition, the mean vasculitis damage index of the group with MetS was significantly higher than in the other patients (4.5 ± 3.3 vs 3.2 ± 2.2, respectively, P = 0.004). Conclusion: The presence of MetS in TAK is associated with increased CVD and disease damage. Awareness and management of MetS can improve disease prognosis in patients with TAK.
Keywords: ROMATOLOJİ; Klinik Tıp; Klinik Tıp (MED); RHEUMATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); cardiovascular disease; metabolic syndrome; Takayasu arteritis; vasculitis; MULTICENTER; cardiovascular disease; metabolic syndrome; Takayasu arteritis; vasculitis